Fear of the dark or dinner by moonlight? Reduced temporal partitioning among Africa's large carnivores. - Cozzi, G; Broekhuis, F; McNutt, J; Turnbull, L; Macdonald, D; Schmid, B (2012)
Africa is home to the last intact guild of large carnivores and thus provides the only opportunity to investigate mechanisms of coexistence among large predator species. Strong asymmetric dominance hierarchies typically characterize guilds of large carnivores; but despite this asymmetry, subdominant species may persist alongside their stronger counterparts through temporal partitioning of habitat and resources. In the African guild, the subdominant African wild dogs and cheetahs are routinely described as diurnal and crepuscular. These activity patterns have been interpreted to result from the need to avoid encounters with the stronger, nocturnal spotted hyenas and lions. However, the idea that diel activity patterns of carnivore species are strongly shaped by competition and predation has recently been challenged by new observations. In a three-year study in the Okavango Delta, we investigated daily activity patterns and temporal partitioning for wild dogs, cheetahs, spotted hyenas and lions by fitting radio collars that continuously recorded activity bursts, to a total of 25 individuals. Analysis of activity patterns throughout the 24-h cycle revealed an unexpectedly high degree of temporal overlap among the four species. This was mainly due to the extensive and previously undescribed nocturnal activity of wild dogs and cheetahs. Their nocturnal activity fluctuated with the lunar cycle, represented up to 40% of the diel activity budget and was primarily constrained by moonlight availability. In contrast, the nocturnal activity patterns of lions and hyenas were unaffected by moonlight and remained constant over the lunar cycle. Our results suggest that other ecological factors such as optimal hunting conditions have shaped the diel activity patterns of subdominant, large predators. We suggest that they are "starvation driven" and must exploit every opportunity to obtain a meal. The benefits of activity on moonlit nights therefore offset the risks of encountering night-active predators and competitors.